QUANTITATIVE ESTIMATION OF FERTILIZER REQUIREMENT FOR CHICKPEA IN THE ALLUVIAL SOIL OF THE INDO-GANGETIC PLAINS - SHIVA AUTAR MISHRA,,; Y. V. SINGH,; DEY, PRADEEP, (The Bioscan, 2015)
A field experiment was conducted in chickpea with integrated use of FYM and fertilizer to estimate the fertilizer requirement for specific yield targets of chickpea at the Agriculture Research Farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi and Uttar Pradesh, India. The chickpea grain and straw yield was significantly increased with the soil test values and fertilizer doses of N, P and K. Based on the experiment the nutrient requirement for producing one quintal of chickpea grain was 6.26 kg of N, 1.12 kg of P2O5 and 3.78 kg of K2O. The percent contribution from soil was 25.41, 40.99 and 19.67, respectively. The contribution of fertilizer towards crop response was 117.03, 35.42 and 45.47 % for N, P and K, respectively and the contribution of FYM towards crop response was 11.43, 5.43 and 10.06 % for N, P and K, respectively. Making use of these basic parameters, fertilizer prescription equations were developed for chickpea (var.) Pusa - 364 and a quantitative estimation of fertilizer doses formulated for a range of soil test values and desired yield targets under NPK alone and with FYM.